Itu Kearifan Lokal Dalam Tradisi Cuci Kampung Pada Masyarakat Serawai Di Kabupaten Bengkulu Selatan - Salsabila, Oktari; Chanafiah, Yayah; Sarwono, Sarwit (Jurnal Korpus, 2025)
The purpose of this research is to explore and describe local wisdom in the tradition of washing the village from adultery, fights and accidents, in the Serawai community in South Bengkulu and to find and interpret local wisdom in the washing village culture in the Serawai community in Bengkulu Regency. South. The research method used in this study is qualitative, leading to an ethnographic approach that emphasizes the process of interpreting the cultural phenomena of a society. Data collection techniques used in this study are observation, interviews, and documentation. The results of this study are that washing the village is a tradition that is carried out in cases of adultery, fights and accidents in the Serawai ethnic community in South Bengkulu. In the implementation process, washing the village is carried out by preparing the tools and materials that have been set, as well as slaughtering chickens and goats and making jambar. This tradition is prepared and carried out at the scene or it can also be at the village hall and in the field. When the banquet is held according to this tradition, young people may not attend but must be parents aged 40 years and over, all food at the banquet may not be taken home but must be eaten during the banquet. The village washing tradition contains local wisdom values, including harmonization, morality, deterrent effect, mutual respect, appreciation, and affection. The tradition of washing the village in this village has never changed since ancient times, nothing has been overlooked in every process from then until now. The purpose of washing the village in the Serawai community is to maintain family and community harmony, establish friendships and be able to teach perpetrators and victims a lesson to be more careful. Keywords: Local Wisdom, Wash Village, Social Institutions